2017
DOI: 10.1152/jn.00176.2017
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill vs. overground walking: different response to physical interaction

Abstract: Rehabilitation of human motor function is an issue of growing significance, and human-interactive robots offer promising potential to meet the need. For the lower extremity, however, robot-aided therapy has proven challenging. To inform effective approaches to robotic gait therapy, it is important to better understand unimpaired locomotor control: its sensitivity to different mechanical contexts and its response to perturbations. The present study evaluated the behavior of 14 healthy subjects who walked on a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 63 publications
4
34
2
Order By: Relevance
“…However, as with many movement science paradigms, it is not known if walker synchronization occurs in real world settings, outside of the laboratory. This is especially relevant for the walking studies in the laboratory: researchers have found a substantial difference in biomechanics between walking on the treadmill and walking on level ground [21,22]. The synchronization of pairs of walkers observed on treadmill might not generalize to real life settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, as with many movement science paradigms, it is not known if walker synchronization occurs in real world settings, outside of the laboratory. This is especially relevant for the walking studies in the laboratory: researchers have found a substantial difference in biomechanics between walking on the treadmill and walking on level ground [21,22]. The synchronization of pairs of walkers observed on treadmill might not generalize to real life settings.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, changes in the evoked TA response may be related to peripheral mechanisms involved in stride time or cadence, as these parameters were significantly different between treadmill and overground walking in the present study. This interpretation is supported by studies that showed biomechanical differences between overground and treadmill gait (Carpinella et al 2010; Chiu et al 2015; Dingwell et al 2001; Lee and Hidler 2008; Ochoa et al 2017). In line with this, these potential changes in evoked TA responses could be due to differences in background electrical activity of dorsal horn spinal neurons.…”
Section: Discussionmentioning
confidence: 63%
“…The vast majority of previous studies investigating gait-related cortical oscillations have been conducted on standard, motorized treadmills. Overground walking, however, has been shown to differ from treadmill walking dynamically and mechanically (Alton et al 1998; Arsenault et al 1986; Carpinella et al 2010; Chiu et al 2015; Dingwell et al 2001; Lee and Hidler 2008; Ochoa et al 2017; Riley et al 2007; White et al 1998). For example, treadmill walking has been found to reduce kinematic variability (Chiu et al 2015; Dingwell et al 2001), increase local dynamic stability (Dingwell et al 2001), affect inter-limb coordination (Carpinella et al 2010), modify lower limb muscle activation patterns, and joint moments and powers (Lee and Hidler 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have to examine walking pairs on a treadmill, which is set at a fixed walking speed (17). Furthermore, biomechanical studies have found that normal ground walking is different from treadmill walking (21,22). The manipulation of walking speed and the very fact of walking on the treadmill might impact the synchronization results and prevent generalization of previous findings.…”
Section: Discussionmentioning
confidence: 99%